Perancangan Tata Udara Menggunakan Metode Cooling Load Tempreture Difference (CLTD) Pada Studi Kasus Proyek X - Madarif Prawibowo; Janatika Putra Perdana; Wiguna Persada Putra; Mohamad Haifan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is related to the design of air conditioning using the Cooling Load Temperature Difference (CLTD) method in the case study of Project X. One of the methods used is the Cooling Load Temperature Difference (CLTD) method. This method considers factors such as wet-bulb temperature, dry-bulb temperature, and air velocity to calculate the room cooling load. This research applies the CLTD method to a case study project in Jakarta with an air conditioning system in office buildings. This case study provides an example of the practical application of the CLTD method that is beneficial for practitioners in the field of air conditioning engineering. To implement the CLTD method, data from field studies such as room conditions, temperature, and humidity of the room and environment are needed. Next, calculations are made using the CLTD formula adjusted to the position of the sun in each room. The CLTD calculation results show that the highest sensible load is in the Boardroom, while the highest latent load is in the Conference Room. The design of the cooling system with the CLTD method shows optimal results and meets the requirements. The AC capacity calculated accurately and considering K4L factors results in an efficient, safe, and environmentally friendly cooling system.